What Is the Safest Intersurgical Interval between Staged Bilateral Total Knee Arthroplasty? A Nationwide Analysis of 20,279 Patients - Pan, Xuankang; Emara, Ahmed K.; Zhou, Guangjin; Koroukian, Siran; Klika, Alison K.; Molloy, Robert M.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2022)
In staged bilateral total knee arthroplasty (BTKA), the intersurgical time is yet to be determined. This study aimed to (1) test for differences in in-hospital metrics between the index and contralateral TKA and (2) determine the safest intersurgical time interval to minimize adverse outcomes after the contralateral surgery. The National Readmissions Database was queried for patients who received staged BTKA (2016–2017). A total of 20,279 patients were included. Demographics, comorbidities, baseline determinants, and intersurgical time between index and contralateral TKAs (≤ 3 month, 4–6 months, 7–9 months, and 10–12 months intervals) were captured. Outcomes included healthcare utilization (length of stay [LOS] and nonhome discharge), in-hospital costs, and in-hospital complications. Outcomes were compared between index versus contralateral surgeries and among contralateral surgeries of various intersurgical intervals. Contralateral surgeries had shorter LOS (2.2 ± 1.9 vs. 2.4 ± 2.0 days; p < 0.001), lower nonhome discharge (n = 2692[13.2%] vs. n = 2963[14.7%]; p = 0.001), and in-hospital costs ($16,476 ± $7,404 vs. 16,774 ± $9,621; p < 0.001), but similar rates of nonmechanical (p = 0.40) complications compared with index TKA. Multivariable regression demonstrated that intersurgical time was not associated with nonmechanical complications or transfusion, or 30-day readmission (p > 0.05, each). Compared with the less than or equal to 3-month interval, the 4 to 6-month interval exhibited highest odds ratio (OR) of any infection (OR: 1.81; 95% confidence interval [CI]: [1.13–2.88]; p = 0.013), urinary tract infection (OR:1.81, 95%CI: [1.13–2.90]; p = 0.014), and any-cardiac complications (OR:1.17; 95%CI: [1.01–1.35]; p = 0.037). Patients in the 10–12-month cohort had lowest odds of posthemorrhagic anemia (OR: 0.84; 95% CI: [0.72–0.98]; p = 0.03). Overall, the second surgery of a staged BTKA has lower healthcare utilization despite similar complication rates. While patients in the 10 to 12-month intersurgical interval had the most favorable overall safety profile, no single interval exhibited consistently lower complications for all measured outcomes. Special care pathways should be optimized to care for patients undergoing staged BTKA.
Keywords: staged; bilateral; TKA; interval; outcomes; nationwide